2017
DOI: 10.4269/ajtmh.16-0880
|View full text |Cite
|
Sign up to set email alerts
|

No Serologic Evidence of Middle East Respiratory Syndrome Coronavirus Infection Among Camel Farmers Exposed to Highly Seropositive Camel Herds: A Household Linked Study, Kenya, 2013

Abstract: High seroprevalence of Middle East respiratory syndrome coronavirus (MERS-CoV) among camels has been reported in Kenya and other countries in Africa. To date, the only report of MERS-CoV seropositivity among humans in Kenya is of two livestock keepers with no known contact with camels. We assessed whether persons exposed to seropositive camels at household level had serological evidence of infection. In 2013, 760 human and 879 camel sera were collected from 275 and 85 households respectively in Marsabit County… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 27 publications
(38 reference statements)
10
46
2
Order By: Relevance
“…Higher in camels > 4yrs p < 0.05 (Munyua et al, 2017) Kenya < 4yrs 36%(n = 319) > 4yrs 80% (n = 830) > 4 < 7yrs 59% (n = 70) > 7yrs 82% (n = 760)…”
Section: Agementioning
confidence: 91%
See 2 more Smart Citations
“…Higher in camels > 4yrs p < 0.05 (Munyua et al, 2017) Kenya < 4yrs 36%(n = 319) > 4yrs 80% (n = 830) > 4 < 7yrs 59% (n = 70) > 7yrs 82% (n = 760)…”
Section: Agementioning
confidence: 91%
“…In a study conducted across Burkina Faso, Morocco and Ethiopia, dromedaries used for milk and meat had higher seroprevalence than those used for transport (Miguel et al, 2017). In most of the studies that stratified by sex, little difference was seen, but in Kenya females had statistically significantly higher seroprevalence than males (93% vs. 81% in one study (Munyua et al, 2017), and 74% vs. 54% in another (Ommeh et al 2018)) whereas males had significantly higher seroprevalence in Egypt and in KSA (72% and 84% in males vs. 66% in females) (Ali et al, 2017b;Kasem et al, 2018b).…”
Section: Sample Population Characteristicsmentioning
confidence: 94%
See 1 more Smart Citation
“…While neither the infection status in persons working with camels nor the risk of transmission was evaluated, studies have indicated that slaughterhouse workers are at an elevated risk of exposure relative to the general population (Muller et al, ). A study conducted in Marsabit County, Kenya, showed that despite 90% sero‐prevalence among camels, there was no serological evidence of MERS‐CoV exposure among pastoralists, suggesting localized MERS virus transmission patterns (Munyua et al, ). Further evaluation of exposure status among persons working with camels would inform development of surveillance and prevention guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…In a study carried out in a single county in Kenya, 47% of camels were found to have antibodies (Deem et al, ). Another study carried out in Marsabit County showed over 90% sero‐prevalence among camels, but none of the humans tested showed presence of antibodies (Munyua et al, ). The true incidence of MERS‐CoV infections in humans may not actually be known, as most patients could be asymptomatic or present with symptoms similar to influenza, the common cold or other infections known to cause respiratory disease.…”
Section: Discussionmentioning
confidence: 97%